Unit cost analysis using the activity-based costing method at the dental and oral clinic, the oral and dental hospital of Andalas University, Indonesia - Suci RAHMASARI; Yurniwati YURNIWATI; Febrian FEBRIAN (Dentistry Faculty, 2022)
The assurance of hospital fee service (unit cost) is still calculated using conventional methods. Themethod is inappropriate because it produces inaccurate rates, providing distorted cost information, either undercosting or over costing, which results in errors in decision making and organizational continuity. Efforts to reducedistortion due to the use of this conventional method is to use a new approach that uses an activity basis, namely,Activity Based Costing, which can accurately measure the costs that come out of each activity to produce the correctrate for each type of service action in hospital. The study aims to analyze unit cost calculations using the activitybasedcostingmethodtosetnewratesandtoexplainpolicyproceduresforthelatestratesframeworkatthedentalandoral clinic of RSGM FKG UNAND. The type of research used is descriptive research with a mixed methodapproach that combines quantitative and qualitative methods. The goal is that data used in mixed method researchwill be more comprehensive, valid, reliable, and objective. The mathematical calculations, the quantitative methodcalculates unit cost with the activity-based costing method. The qualitative method analyzes information about feesetting procedures by conducting in-depth interviews. The quantitative research results obtained the unit cost valuefor services with the most visits, including composite fillings and IDR. 157.099.78, scaling is IDR.134,162.95, and rootcanal treatment is IDR.167,815.94. Results of qualitative research through in-depth interviews obtained that insetting the new rates through the structural levels that apply at Andalas University. The recent rate decisions at thedental and oral polyclinic services of RSGM FKG UNAND are in the discussion stage of the rectorate leadership.The new rates are based on unit cost calculations using the activity-based costing method plus a margin or expectedprofit.KEYWORDS: Activity-based costing, unit cost, rates, policy rates